Loading supplies on to steamer in Skagway harbor, Alaska, 1897. - La Roche, Frank (1897)
Caption on image: ""Skagua Alaska"" ""We are going to be in it any way the cat jumps"". This expression was made use of by a prominent man in Skaguay and it practically conveys the intention of the townsmen in general. Not only are they discussing the best means of competing for the patronage of the miners on the overland trip, but they are rapidly developing all kinds of conveniences. The small boat in the picture is occupied in ferrying goods to the steamer which is at anchor waiting for high tide before proceeding on its journey. The raft beside the steamer is an odd looking structure, but its usefulness can be readily appreciated by those who have had any experience in this neighborhood."" (Frank La Roche, En Route to the Klondike, 1898) Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number